Larutan Sabun Sebagai Alternatif Pengganti Sulfolyser Pada Pemeriksaan Hemoglobin Metode SLS-Hemoglobin - Muhammad Ahyat Ridhoni; Siti Rachmah; Rusmini (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Hemoglobin examination constitutes an essential procedure in clinical diagnosis, with the SLS-hemoglobin method serving as a non-toxic alternative to cyanmethemoglobin. However, the limited availability of sulfolyser has prompted investigations into the use of soap solutions, which also contain sodium lauryl sulfate (SLS), as a potential substitute. This study employed a quasi-experimental design with a posttest-only control group on 24 blood samples, comparing the standard sulfolyser reagent with three types of commercial soaps. The analysis revealed significant differences in hemoglobin levels across groups (p < 0.001), with dishwashing soap yielding values most comparable to the control, albeit still statistically lower. These findings confirm that soap solutions are capable of lysing erythrocytes and forming hemoglobin complexes, though variations in product composition constrain the consistency of results. Practically, soap demonstrates potential as a more accessible and cost-effective alternative reagent; however, its application requires concentration standardization to ensure diagnostic validity.